MODAL SOSIAL MASYARAKAT DI KAWASAN PENYANGGA TAMAN NASIONAL KUTAI (TNK) DALAM PENGEMBANGAN EKOWISATA - Poppy Oktadiyani; E.K.S Harini Muntasib; Arzyana Sunkar (Media Konservasi, 2013)
Kutai National Park (KNP) is a national park that is bordered by a coal mining company, PT. Kaltim Prima Coal (PT. KPC).  Located between the park and the company are communities living in the Kabo Jaya Hamlet of Swarga Bara Village and G III Hamlet of Singa Gembara Village who were economically dependent on this company.  A main concern prior to the post-mining period in 2021 is the lost of source of livelihood which could trigger the exploitation of the national park.  Therefore, with the natural resources available in P revab-Mentoko KNP, Tanjung Bara Beach, and Tanjung Bara Mangrove, as alternative sources of livelihood, the idea of utilizing these resources for ecotourism purposes arose to prepare the community for PT. KPC’s post-mining period. The research aims to study the social capital of ecotourism development in the KNP buffer zone. Data were collected using several methods including field observation, participative observation, in depth interview, and literature study. The research used several methods of analysis including Social Capital Assesment Tools (SCAT) to assess the community’s social capitals, Confirmatory Factor Analysis (CFA) to assess the relationships between social capital variables, and descriptive analysis to evaluate each stakeholder’s ecotourism development policies.  Social capital adequacy value for Kabo Jaya Hamlet of Swarga Bara Village was 173 (sufficient) and that of G III Hamlet of Singa Gembara Village was 159 (insufficient). Ecotourism development was less difficult in Kabo Jaya Hamlet based on its existing social capital with the Kabo Jaya Ecotourism Group. Every element of social capital in G III Hamlet significantly affect the social capital, and the most significant element is care for others and the environment. Keywords:  Community, ecotourism, G III Hamlet, Kabo Jaya Hamlet, Social Capital.